Verification of the Walkley Black Method Test for Determination of Organic Carbon Elements in Palm Oil Empty Fruit Bunch Waste Fertilizer - Wakhid Khoirul Umar; Fandika Agustiyar; Aulia Rahma (Eksergi, 2022)
Verification of the organic carbon method on organic fertilizer from Palm Oil Empty Fruit Bunches (TKKS) waste using a UV-Vis Spectrophotometer has been carried out. The determination of this OPEFB fertilizer refers to the AOAC (2000) with the Walkley Black method. The results of the organic carbon test on OPEFB fertilizer show the correlation coefficient (r) value obtained is 1.0000, and the % relative standard deviation (RSD) value of 0.4022% means that the value is below 2/3 CV Horwitz of 4.7230. accuracy with a value of 106.99%. The method limit value (LOD) is 2.4531, and the quantization limit value (LOQ) is 8.1769. The instrument limit value (LOD) is 2.4990, and the quantification limit value (LOQ) is 8.3299; the test results indicate that it has complied with the conditions with acceptance. The test results for determining organic carbon in OPEFB fertilizer using the Walkley Black method with UV-Vis Spectrophotometer showed valid results, so the method could be used.